2014
DOI: 10.5539/ibr.v7n3p137
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation of Free Cash Flow Hypothesis: Evidence from Jordanian Capital Market

Abstract: This study aims to investigate free cash flow hypothesis proposed by Jensen (1986). Data pertaining to 102 non-financial firms listed on ASE during the period of 1998-2009 are analyzed using pooled and panel data methods. Contrary to Jensen (1986) proposition, we found that debt and dividend are not substitute techniques for mitigating agency costs of free cash flow in the Jordanian capital market, rather, they are complementary to each other. However, debt is used more than dividend for stability consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Free cash flow refers to the cash resources over and above the amount needed to finance approved investment activities considered to possess a positive net present value (Zurigat et al, 2014). The free cash flow theory was proposed by Jensen (1986), who argued that, for firms that are more likely to have high amounts of excess funds but without apparent investment opportunities, debt becomes an efficient way of resolving the agency costs associated with free cash flow.…”
Section: Free Cash Flow Theorymentioning
confidence: 99%
“…Free cash flow refers to the cash resources over and above the amount needed to finance approved investment activities considered to possess a positive net present value (Zurigat et al, 2014). The free cash flow theory was proposed by Jensen (1986), who argued that, for firms that are more likely to have high amounts of excess funds but without apparent investment opportunities, debt becomes an efficient way of resolving the agency costs associated with free cash flow.…”
Section: Free Cash Flow Theorymentioning
confidence: 99%
“…It has also affected performance (Risman, A., & Parwoto, A. S. S., 2021). The free cash flow hypothesis is the basis on which agency theory is Zurigat, Sartawi & Aleassa (2014) presented their argument on the logic of agency theory. Poor management has a direct effect on the well-being of the company.…”
Section: Introductionmentioning
confidence: 99%
“…Managers of listed companies on ASE have only a 4 per cent investment in these companies, which makes agency conflicts more severe. Also, Jordan adopted financial liberalization in 1990, which, consequently, has led to a boost in the flexibility given to managers in controlling the cash holding (Zurigat et al, 2014). Alnawaiseh et al (2017) indicated that many listed companies have free cash flow, but that only 15 per cent of Jordanian companies employed free cash flow efficiently.…”
Section: Introductionmentioning
confidence: 99%